cyclic ( a , b , c ) ∑ ( 1 + lo g a b c 1 ) = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Using lo g a b = ln a ln b and ln ( a b ) = ln a + ln b summation can be written as:
cyc ∑ 1 + ln a ln b c 1 = cyc ∑ ln a + ln b c ln a = cyc ∑ ln a + ln b + ln c ln a = ln a + ln b + ln c cyc ∑ ln a = 1
Yeah C O O L
Nice thinking good job.
how do you color words?
cyclic ( a , b , c ) ∑ 1 + lo g a ( b c ) 1 = cyclic ( a , b , c ) ∑ lo g a ( a ) + lo g a ( b c ) 1 = cyclic ( a , b , c ) ∑ lo g a ( a b c ) 1 = cyclic ( a , b , c ) ∑ lo g a b c ( a ) = lo g a b c ( a ) + lo g a b c ( b ) + lo g a b c ( c ) = lo g a b c ( a b c ) = 1
The equation above is true for any positive values of a,b,c. (guess) So just sub in a=b=c=2 and you get the answer
If it's about solving a problem--then be it a = b = c for this case (take 2 for example-or anything valid for this function).
Problem Loading...
Note Loading...
Set Loading...
cyclic ( a , b , c ) ∑ ( 1 + lo g a b c 1 )
= 1 + lo g a b c 1 + 1 + lo g b c a 1 + 1 + lo g c a b 1
= 1 + lo g a b c 1 + 1 + lo g a b lo g a c a 1 + 1 + lo g a c lo g a a b 1
= 1 + lo g a b c 1 + ( lo g a b lo g a b + lo g a c + lo g a a ) 1 + ( lo g a c lo g a c + lo g a a + lo g a b ) 1
= 1 + lo g a b c 1 + 1 + lo g a b c lo g a b + 1 + lo g a b c lo g a c
= 1 + lo g a b c 1 + lo g a b c
= 1